CMCE Propolis Extract Improve Caspase 3 Expressions of The Hepatocytes and IL-6 Levels in Rats Exposed with CCl4 - Firdaus, Chalid; Chodidjah, Chodidjah; Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Liver plays an important role in the metabolic processes possibly exposed to the toxic materials. One of those hepatotoxic substances is carbon tetrachloride. The propolis extract contains the balsamic active substances, CAPE compounds and flavonoids. Flavonoids can prevent from the apoptosis and reduce the inflammation.Objective: To validate propolis extract’s (CMCE method) ability in improving caspase 3 expressions of hepatocytes and IL-6 levels in Wistar male rats induced with carbon tetrachloride.Methods: An experimental study with a post-test only control group design applied to the study. The research subjects were 28 male Wistar rats, divided into four groups. The negative control group (CN-G) was only injected with CCl4, while the experimental groups were administered with the CMCE propolis at the dosages of 3.6 mg/200g (CM3-G), 7.2 mg/200g (CM7-G), and 14.4 mg/200g (CM14-G). The CMCE propolis extract was administered for 14 days and on day 14, the CCl4 was then given. The caspase 3 expression of hepatocytes was measured using HE liver cell preparations, while the IL-6 levels were measured using ELISA method.Results: The results of Mann-Whitney U statistical analysis showed that the hepatocytes’ caspase 3 expressions in CM14-G (2.77 ± 0.531), CM7-G (3.14 ± 0.378), and CM3-G (4.22 ± 0.690) were lower than those in CN-G (5.43 ± 0.535), p<0.05. Meanwhile, the Post Hoc LSD analysis Results showed that IL-6 levels in CM14-G (55.032 ± 9.336), CM7-G (78.362 ± 8.313), and CM3-G (114.975 ± 10.359) were lower those in CN-G (180.301 ± 5.428), p<0.05.Conclusion: the administration of propolis extract (CMCE method) improve the caspase 3 expressions of hepatocytes and Il-6 levels in Wistar male rats induced with carbon tetrachloride.